Development of an STM32 Microcontroller Training Kit for Microcontroller Programming Based on Project-Based Learning to Enhance Understanding of Microcontroller Programming - A Khotib Tri Handoko; Yeri Sutopo; Sri Sukamta (Universitas Negeri Semarang, 2026)
This research addresses the competency gap between the graduation outcomes of Electronic Engineering Vocational High School (SMK) students and industry requirements. The theoretical nature of the existing curriculum has resulted in a lack of practical skills among students. The objective of this study was to develop an STM32 Microcontroller Training Kit integrated with Project-Based Learning (PjBL) and assess its feasibility, practicality, and effectiveness in improving learning outcomes in Electronic Engineering competencies. The study used a Research and Development approach with the ADDIE model. The research subjects were 11th-grade students of the Industrial Electronic Engineering program at SMK Negeri 1 Kalinyamatan, divided into an experimental group and a control group. Data were collected through observations, interviews, expert validation, user response questionnaires, and pre-test and post-test assessments. The validation results indicated that the product was highly feasible, with a Content Validity Index (CVI) of 0.97 from media experts and 0.92 from subject matter experts. Practicality testing yielded a CVI score of 0.95, classified as very practical. The effectiveness test using an Independent Sample T-Test revealed a significance value of 0.00<0.05; the post-test mean score for the experimental group was 85.00, significantly higher than the control group’s 68.33. The N-Gain analysis showed a 69.89% improvement in the experimental group, indicating that the intervention was moderately effective. In conclusion, the STM32-based PjBL Training Kit is valid, practical, and effective for improving the competencies of SMK students in alignment with industry standards within vocational electronic education.